Efeito hipotensor do extrato aquoso de alpiste (Phalaris canariensis L.) em ratos - Balbi, A. P C; Campos, K. E. [UNESP]; Alves, M. J Q F [UNESP] (My University, 2008)
The plant species Phalaris canariensis, known as canary grass, is widely used in folk medicine as diuretic, as well as in culinary and animal feed. In this study, the effect of P. canariensis aqueous extract (AE) on water flow (V) and sodium renal excretion (Qe (Na+)) was evaluated in anesthetized Wistar rats. Arterial pressure alterations (AP) were also assessed. Two groups were studied: Control group (CON) - oral administration of 1.0 mL distilled water, and Experimental group (EA) - oral administration of 1.0 mL P. canariensis aqueous extract 40%. Rats were anesthetized and subjected to cannulation of trachea (for better pulmonary ventilation), left carotid artery (for arterial pressure measurement) and urinary bladder (for urine collection). Control animals did not present significant alterations (p>0.05) in all analyzed parameters after water administration. EA group had a significant arterial pressure reduction at 60 minutes (31.4%) and 90 minutes (49.1%) after the extract administration (p<0.05). Renal parameters did not have any significant alteration (p>0.05). In this study, P. canariensis aqueous extract had a hypotensive effect in anesthetized Wistar rats, without renal alterations.
Hypotensive effect of canary grass (Phalaris canariensis L.) aqueous extract in rats
Keywords: Arterial pressure; Canary grass; Phalaris canariensis; Wistar rat; antihypertensive agent; Phalaris canariensis extract; plant extract; unclassified drug; animal experiment; antihypertensive activity; arterial pressure; cannulation; carotid artery; controlled study; male; nonhuman; Phalaris; rat; sodium excretion; urinary excretion; water flow; Animalia; Phalaris aquatica; Rattus; Rattus norvegicus